Determinants of Factors Associated With Community Demand for Health Services at Pintu Padang Health Center, South Tapanuli Regency - Rambe, Normayanti; Nasution, Lisna Khairani; Yusuf, Susi Febriani (International Journal of Public Health Excellence (IJPHE), 2023)
Demand for health services is one of the most important and influential factors in a health service, Demand (demand) can be in the form of goods or services used or purchased by patients. The purpose of this study was to determine the relationship between information technology, values and norms and accessibility to health services at the Pintu Padang Health Center. Measurements in this variable were carried out using a questionnaire. This type of quantitative research with a Cross Sectional approach. The sample was 365 respondents. Sampling used the Accidental Sampling method. Univariate and bivariate analysis. The results of data analysis showed that there was a significant relationship between information technology and public demand with a p-value of 0.000 (<0.05), there was a significant relationship between values and norms to public demand with a p-value of 0.000 (0.05), there was a significant relationship between accessibility and public demand with a p-value of 0.000 (0.05). Further improve services that can make it easier for patients to get health services.